Smart Contract-Based Agricultural Food Supply Chain Traceability - Pathan Yaseen; Dr.Nagamani Chippada (Utilitas Mathematica, 2025)
The agricultural industry now deals with major obstacles to make its food supply chain transparent while ensuring traceability and efficiency. The need for innovative solutions has become essential because issues including food fraud and inefficient product tracking and agricultural quality inspection without visibility and rising customer requirements for verified sourcing emerged. By implementing blockchain technology agricultural supply chains can present transformative benefits to achieve data veracity and increase transparency and operational efficiencies. The project establishes a Smart Contract-Based Agricultural Food Supply Chain Traceability system powered by blockchain which enables real-time origin and status tracking for everyone from farmers to consumers in the agricultural value chain. The system implements smart contracts enabled with automated functionality through code-based implementations of agreement terms. Smart contracts within this system will operate across agricultural supply chain levels to avoid human mistakes while cutting down delivery times by removing unnecessary middlemen. All transaction activities throughout the agricultural value chain from crop harvesting through storage and processing until delivery will be stored permanently on blockchain records accessible to every stakeholder. Every participant benefits from a trustworthy and secure system of record keeping which tracks food products from fields through distribution points to consumers ensuring strengthened trust and accountability. The aim of the traceability system is to deliver instant access to details about product placement and quality status as well as temperature monitoring and organic and sustainable farming certification records. Traceability plays a vital role in stopping contaminated food from spreading as well as helping reduce food waste and promote fair trade operations. Blockchains decentralized structure reduces the possibility of fake data entry while also making all consumer-relevant information easily verifiable and reliable. The project investigates Internet of Things (IoT) devices which supply immediate environmental data about temperature and humidity levels that serve as essential indicators for food safety throughout shipment and storage. Every time IoT devices detect predetermined thresholds the smart contracts automatically launch established actions including automated alert notifications or hazardous condition remedies. The system operates with increased automation as well as enhanced operational efficiency. Essential to the modern agricultural industry is integrity, efficiency, and trust of the food supply chain in food safety and consumer confidence. This project calls for a smart contract driven blockchain solution for traceability in agricultural food supply chain. As a system it utilizes the travel of agricultural products as it leaves the farm, record this and monitor based on its use of the decentralized, immutable and transparency-oriented tendency of the blockchain technology. Smart contracts are used to automate the main deals, to enforce compliance with standards, and to reduce the necessity in the intermediary presence. All stages of the supply chain, from production and processing down to distribution and retail, are securely catalogued on the blockchain, thus making it possible to track and verify food at every stage; the source, handling and quality certifications. The solution improves accountability of stakeholders, minimizes the occurrence of fraud, and makes consumers in a position to gain credible product information This project is proposing a blockchain based traceability solution by the use of smart contracts in order to improve the integrity and visibility over the agricultural food supply chain. With the help of the decentralized and irreversible nature of blockchain technology, it is possible for the system to have real time monitoring of agricultural products from the farm to the fork. Smart contracts are deployed to automate and enforce compliance at all stages of the supply chain from production and supply through processing, distribution to retail. Every transaction and storage of custody is stored in a blockchain, which guarantees data transparency and minimizes risks of manipulation. The proposed solution enables the stakeholders to obtain verifiable information on the origin, quality, and movement of their products while providing the consumers with the same information and powers them to choose what they want for their consumption, improve their logistics, reduce wastage and be well prepared when there are food recalls. This project shows the promise of blockchain and smart contracts to create a safer, more transparent & credible food supply-chain.